TOK: developing a tangible platform for storytelling - Sylla, Cristina (2011)
This paper describes a first study of a tangible interface, consisting of a platform and a set of picture cards that children can use to create stories. The handling of the picture cards has shown to be highly motivating and engaging, helping children to build a storyline creating logical relations among different characters and objects. The interface works like an experimental space where children can play with the language and simultaneously reflect over it, individually or in a collaborative process. We present the design of the first prototype and the data collected with two groups of five years old preschoolers and report our findings regarding the interaction design, as well as a reflection over future work.